Characterizing Teachers' Verbal Scaffolds to Guide Elementary Students' Creation of Scientific Explanations. (5th November 2013) - Songer, Nancy Butler; Shah, Ashima Mathur; Fick, Sarah
Abstract : Scaffolding is a complicated construct that can take many forms, including both written and verbal forms. This research study focused on three elementary science classrooms where students were using a series of written scaffolds to guide explanation building. In each classroom, data were collected to document and study an additional type of scaffold, verbal scaffolds that the teachers provided to complement the written scaffolds. Findings suggested that some types of verbal scaffolds, such as navigational guidance, were universal and therefore cut across all three grade levels. On balance, other verbal scaffolds were more common with younger students in association with their first explanation‐building science unit, such as a verbal scaffold that turned an open‐ended question into a few multiple‐choice options. Through the characterization of the types and range of verbal scaffolds that teachers say, both in general and in response to audience, we can gain insights to inform both curricular design and professional development toward supported explanation building across target audience, time, and topic.